1957
DOI: 10.1302/0301-620x.39b2.268
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondritis Dissecans of the Hip

Abstract: 1. The pathological anatomy of osteochondritis dissecans of the hip is described, and its causation is discussed. 2. Eight new cases are reported. 3. The problems of treatment are considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

1962
1962
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…The first published reference of osteochondritis dissecans of the hip was by Haenisch in 1925 with several reports to follow soon thereafter [13]. It is a multifactorial condition of uncertain etiology that is often an incidental finding on routine radiographic evaluation of the involved joint.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first published reference of osteochondritis dissecans of the hip was by Haenisch in 1925 with several reports to follow soon thereafter [13]. It is a multifactorial condition of uncertain etiology that is often an incidental finding on routine radiographic evaluation of the involved joint.…”
Section: Discussionmentioning
confidence: 99%
“…The natural history of symptomatic osteochondritis dissecans of the hip is poor [8,13,20] with limited treatment options. Unlike osteochondritis dissecans of the knee, lesions of the hip most often involve the weightbearing dome and remain intact in its crater.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If it is accepted that the not uncommon Perthes' disease is of the same pathological process with that of osteochondritis dissecans, Smillie (1960) suggested that the rarity of this condition in the hip could be explained by the fact that it is a localized form of Perthes' disease occurring at a later stage of development. Guilleminet & Barbier (1957) also thought that femoral capital necrosis of the type of osteochondritis dissecans of the hip in the later years of childhood might be a transitional phase between Perthes' and Konig's disease. As for the occurrence of osteochondritis dissecans following coxa plana, malformation of the femoral head after this condition could probably be a predisposing factor.…”
Section: Discussionmentioning
confidence: 99%
“…Its use has been reported in the treatment of rheumatoid synovitis, 2,3 synovial chondromatosis, 4 pigmented villonodular synovitis, 5 labral tears 6 and in joint debridement. [7][8][9][10] It can be carried out through an anterior, lateral or posterior approach. Epstein 11,12 favoured primary open reduction by the posterior approach for traumatic dislocations.…”
mentioning
confidence: 99%